PENGEMBANGAN WAKAF BERBASIS SUKUK DALAM PEMBERDAYAAN TANAH TIDAK PRODUKTIF DI INDONESIA PERSEPEKTIF HUKUM ISLAM - Irawan, Feri (Mu'amalatuna: Jurnal Ekonomi Syariah, 2020)
ABSTRACT Waqf has more flexibility than zakat so that the form of waqf will continue to evolve according to the times. The sukuk-based waqf innovation was launched in early 2017 by the Government in order to maximize the potential of waqf land in Indonesia, it's just that the legal aspects of the sukuk itself are legally still khilafiah. The methodology used is a qualitative research method through literature, with the type of normative juridical research and secondary data sources that are collected by documentary methods and interviews and then analyzed descriptively qualitatively so that the synchronization level and the feasibility of norms are known. The results of this study show that the waqf and sukuk stand from 2 different objectives of the contract, namely the tabarru and tijaroh contracts, which are combined in order to present greater maslahah value. The legal position of this sukuk-based waqf if it is built on a sukuk ijarah agreement which is similar to bai al-wafa according to the number of scholars, is prohibited, except for the Hanafi school of thought that allows it. This is in line with the DSN fatwa on sukuk and Articles 112-113 of KHES regarding bai al-wafa. Statement of opinion in the context of this fiqh, it is necessary to pay attention to the clear regulatory aspects that underlie this sukuk-based waqf, pay attention to the administration of waqf assets both land and building certificates and waqf certificates and it is necessary to pay attention to aspects of sharia legality so that the main purpose of waqf for the benefit of the people can still be achieved without reducing the value or form of the waqf assets. Keywords: waqf, sukuk, Islamic law  ABSTRAKWakaf memiliki fleksibilitas yang lebih dibandingkan zakat sehingga bentuk wakaf akan terus berkembang sesuai dengan perkembangan zaman. Inovasi wakaf berbasis sukuk yang diluncurkan di awal 2017 oleh Pemerintah dalam rangka memaximalkan potensi tanah wakaf di Indonesia, hanya saja aspek hukum sukuk itu sendiri secara hukum masih khilafiah. Metodologi yang digunakan adalah metode penelitian kualitatif melalui studi kepustakaan, dengan jenis penelitian yuridis normatif dan sumber data sekunder yang dikumpulkan dengan metode dokumenter dan wawancara lalu dianalisis secara deskriptif kualitatif sehingga diketahui taraf sikronisasi dan kelayakan norma. Hasil penelitian ini bahwa wakaf dan sukuk berdiri dari 2 tujuan akad yang berbeda yaitu akad tabarru dan tijaroh, yang digabungkan dalam rangka menghadirkan nilai maslahat yang lebih besar. Kedudukan hukum wakaf berbasis sukuk ini jika dibangun diatas akad sukuk ijarah yang hampir serupa bai al-wafa menurut jumhur ulama diharamkan, kecuali madzhab hanafi yang membolehkannya. Hal ini yang selaras dengan fatwa DSN tentang sukuk dan Pasal 112-113 KHES tentang bai al-wafa. Terlepas dari perbedaan pendapat dalam konteks fiqh ini, perlu diperhatikan aspek regulasi yang jelas yang melandasi wakaf berbasis sukuk ini, memperhatikan perapihan administrasi aset wakaf baik sertifikat tanah dan bangunan maupun sertifikat wakaf dan perlu diperhatikan aspek legalitas syariah agar tujuan utama wakaf untuk kemaslahatan umat tetap dapat tercapai tanpa mengurasi nilai ataupun wujud dari asset wakaf. Kata kunci: Wakaf, sukuk, hukum Islam